ADHD - Hammerness, Paul Graves. 4 0 16; 5 (Westport, Connecticut : Greenwood Press, 2009)
Chronicles the history of attention deficit hyperactivity disorder and its treatments, and draws from scientific literature to explain what ADHD is, how it is diagnosed, why children get ADHD, the process of drug development, treatments, and other aspects of the condition.
Includes bibliographical references and index.
Young Adult.
Keywords: 2 -- 0; 6; Attention-deficit hyperactivity disorder.;Attention-deficit disorder; 20; 2